TEACHINGS OF THE MASYARAKAT TANPA RIBA IN THE LIGHT OF THE SOCIOLOGY OF KNOWLEDGE - Devi Ernantika; Luhur Prasetiyo; Royyan Ramdhani Djayusman (IAIN Ponorogo, 2022)
AbstractThe purpose of this study is to explore the attitude background of the Society Without Usury (herein after written MTR). The MTR rejects the existence of interest and banks. MTR is a community committed to developing a business without usury, without debt, and without contracts that are not under sharia. One form of this commitment is that MTR members refuse to pay bank debts and interest. Meanwhile, the banks believe that the customer should pay the debt and interest according to the contract. This research is qualitative. Data were obtained through in-depth interviews, observations, and documentation. Key informants are administrators and members of the MTR. Based on the results of the study, it can be concluded that the MTR community has three qualification meanings in the sociology of knowledge, namely objective meaning, which can be seen from community understanding and community beliefs regarding usury, especially bank interest. The behavior of MTR residents is formed due to external factors, namely the stimulus from the family environment that has previously joined the MTR community. The expressive meaning of the MTR community is the meaning impregnated by every MTR citizen who is integrated with the behavior of avoiding usury and doing other teachings, such as improving the creed, improving relations with the social environment, still seeking knowledge, especially the science of good peace, and others. Meanwhile, the documentary meaning is a material activity manifested in religious practices and rituals. AbstrakTujuan dari penelitian ini adalah untuk mendalami latar belakang sikap kelompok Masyarakat Tanpa Riba (selanjutnya ditulis MTR) yang menolak keberadaan bunga dan bank. MTR adalah sebuah komunitas yang mempunyai komitmen mengembangkan bisnis tanpa riba, tanpa utang, tanpa akad-akad yang tidak sesuai syariah. Salah satu bentuk komitmen tersebut adalah anggota MTR menolak untuk membayar hutang bank beserta bunganya. Sedangkan pihak bank berpandangan bahwa nasabah memiliki kewajiban untuk membayar hutang beserta bunganya sesuai kesepakatan kontrak di awal. Penelitian ini bersifat kualitatif. Data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi. Informan kunci adalah pengurus dan anggota MTR. Berdasarkan hasil penelitian dapat disimpulkan bahwa komunitas MTR memiliki tiga makna kualifikasi dalam sosiologi pengetahuan, yakni makna objektif yang dapat dilihat dari pemahaman komunitas dan keyakinan komunitas mengenai riba terutama bunga bank. Perilaku warga MTR terbentuk karena faktor eksternal, yakni stimulus dari lingkungan keluarga yang sudah terlebih dahulu bergabung dengan komunitas MTR. Makna ekspresif dari komunita MTR adalah makna yang diresapi oleh setiap warga MTR yang terintegrasi dalam perilaku menghindari riba dan melakukan ajaran lainnya, seperti memperbaiki akidah, memperbaiki hubungan dengan lingkungan sosial, tetap mencari ilmu terutama ilmu bermuamalah yang baik, dan lain-lainnya. Sementara, makna dokumenter, yakni sebagai kegiatan material yang terwujud dalam bentuk praktik agama dan ritualnya.